A Systematic Review of the Implementation of Lean Six Sigma Tools to Improve the Logistics of Retail Businesses - Melgar Torres, Renzo (2023)
Currently, retail businesses must be as competitive as possible, and for this, their logistics system must be efficient and optimal; however, it is known that these have various problems such as longer delivery times, product delivery errors, offering a quality of service that meets customer expectations, etc. To solve these problems, the implementation of Lean Six Sigma tools was proposed, and a systematic review of the literature was carried out to determine which Lean Six Sigma tool is the most frequent and expose the benefits provided to the logistics system of retail businesses. A combination of keywords was used in prestigious databases such as Web of Science, Scopus and Pro-Quest to search for academic articles. On the other hand, for the analysis and classification of each article, categories and subcategories were used for synthesizing the information from each research work. To determine which tool is the most frequent, the number of articles were quantified if they applied an LSS tool and met the inclusion and exclusion criteria. Regarding the results, after carrying out the systematic review of the literature, the DMAIC tool was the most frequent and provided benefits such as a reduction in the number of complaints, a reduction in lead time, operations costs reduction, among others.